From Pitch to Console: Exploring the Role of Football eSports in the Development of Young Footballers - Rosario Ceruso; Genoveffa De Cesare; Arben Kaçurri; Agron Kasa; Giampiero Merati (Physical Education Theory and Methodology)
Objectives. The study aimed to analyse the impact of football eSports on the perceptions of young footballers, focusing on the key components, namely motivation, technical and tactical skill development, and career choices in the football context.